2014
DOI: 10.3233/jad-132693
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Subset Analysis of Copy Number Variation Association with Age at Onset of Alzheimer's Disease

Abstract: Genetic heterogeneity is a common problem for genome-wide association studies of complex human diseases. Ordered-subset analysis (OSA) reduces genetic heterogeneity and optimizes the use of phenotypic information, thus improving power under some disease models. We hypothesized that in a genetically heterogeneous disorder such as Alzheimer’s disease (AD), utilizing OSA by age at onset (AAO) of AD may increase the power to detect relevant loci. Using this approach, 8 loci were detected, including the chr15: 30,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In a study on the AD neuroimaging initiative samples, significant higher burden of CNV-region deletions was found in mild cognitive impairment (MCI) and AD cases compared to controls (Guffanti et al, 2013). In two separate studies on the effect of CNV on the AAO of AD, CNVs in CPNE4 and CHRFAM7A were found to be potential risk for AD (Szigeti et al, 2014(Szigeti et al, , 2013.…”
Section: Cnv Studiesmentioning
confidence: 96%
“…In a study on the AD neuroimaging initiative samples, significant higher burden of CNV-region deletions was found in mild cognitive impairment (MCI) and AD cases compared to controls (Guffanti et al, 2013). In two separate studies on the effect of CNV on the AAO of AD, CNVs in CPNE4 and CHRFAM7A were found to be potential risk for AD (Szigeti et al, 2014(Szigeti et al, , 2013.…”
Section: Cnv Studiesmentioning
confidence: 96%
“…[15][16][17][18] Association testing within candidate genes, 19 GWAS 12,20 and linkage studies 4,5,8 have found evidence for additional modifiers of AAO of AD in samples with and without causal EOAD variants. Several of these loci are significant or suggestive across independent genomescans for AAO modifiers, including 5q15, 21,22 7q31. 33,5,6,23 8p22, 12,24 9q33.1, 6,23 13q33.…”
Section: Introductionmentioning
confidence: 99%
“…Association testing within candidate genes (Leduc et al , 2015), GWAS (Lalli et al , 2015), and linkage studies (Lee et al , 2015, Marchani et al , 2010, Zhao et al , 2013) have found evidence for additional modifiers of AAO of AD in samples with and without causal EOAD variants. Several of these loci are significant or suggestive across independent genome-scans for AAO modifiers, including 5q15 (Lee et al , 2008, Szigeti et al , 2014), 7q31.33 (Choi et al , 2011, Marchani et al , 2010, Wang et al , 2015), 8p22 (Naj et al , 2014, Szigeti et al , 2013), 9q33.1 (Choi et al , 2011, Wang et al , 2015), 13q33.3(Lee et al , 2008, Naj et al , 2014), and 20p12.3 (Velez et al , 2016a, Wang et al , 2015). One of these loci, 7q31.33, is supported by analyses of Volga German PSEN2 families affected by EOAD (Marchani et al , 2010) and independent LOAD data sets with European ancestry (Choi et al , 2011, Wang et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that autism and schizophrenia share several rare CNVs [Carroll and Owen, 2009; Heinzen et al, 2010]. Genome-wide scans for CNVs have been conducted recently to identify genetic factors associated with AD [Heinzen et al, 2010; Shaw et al, 2011; Ghani et al, 2012; Rovelet-Lecrux et al, 2012; Swaminathan et al, 2012; Chapman et al, 2013; Guffanti et al, 2013; Szigeti et al, 2013, 2014]. More recently, some studies have evaluated CNVs in AD+P.…”
Section: Introductionmentioning
confidence: 99%